The functioning and transformation of press self-regulation in a new democratic media landscape: a case study of the South African Press Ombudsman - Kumwenda, Olivia Vitumbiko (My University, 2010)
Abstract Press self-regulation has provoked debate and drawn criticism in South Africa since the practice was started over four decades ago following threats of statutory regulation. The practice has gone through various permutations to suit prevailing social and political environments in the country. Focusing on the press ombudsman system as a case study, this research examines the functioning and transformation of press self-regulation in response to the changing media landscape in a democratic South Africa. The research utilises social responsibility theory of the press to provide a theoretical understanding on the need for the press to be self-regulatory. Document analysis and in-depth interviews are the main data collection methods utilised in the study. Using thematic content analysis, the study then draws on themes emerging from the findings to address the research question. The findings show that people from across the range in South Africa utilise the system, albeit to varying extents, and that the system has fairly handled complaints with rulings evenly going for and against the press. The findings also show that through amendments to the Press Code and procedures for handling complaints, the press self-regulatory mechanism has transformed mainly owing to democratic constitutional and legal requirements and public expectations. However, the system has been resistant to some of the criticism, hence there still remains public and political pressure for the system to address the concerns.